Emerging regulatory mechanisms of noncoding RNAs in topologically associating domains - Yeo, Samuel Jianjie (2023)
Topologically associating domains (TADs) are integral to spatial genome organization, instructing gene expression, and cell fate. Recently, several advances have uncovered roles for noncoding RNAs (ncRNAs) in the regulation of the form and function of mammalian TADs. Phase separation has also emerged as a potential arbiter of ncRNAs in the regulation of TADs. In this review we discuss the implications of these novel findings in relation to how ncRNAs might structurally and functionally regulate TADs from two perspectives: moderating loop extrusion through interactions with architectural proteins, and facilitating TAD phase separation. Additionally, we propose future studies and directions to investigate these phenomena.